Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India. Issue 2 (7th February 2020) - Aneesh Kumar, K. V.; Deepa, K. P.; Muhammed Rafeeq, M. M.; Sree Renjima, G.; Manjebrayakath, Hashim; Smitha, B. R.; Saravanane, N.; Prabhakaran, M. P.; Sanjeevan, V. N.; Sudhakar, M.
ABSTRACT: Near reef abundance and coast–offshore distribution of tuna larvae around Minicoy Island were studied based on three cruises carried out on board FORV Sagar Sampada during 2014–15. The samples were collected by oblique tows using bongo twin nets (300 micron) for three seasons (Fall inter-monsoon (FIM), Spring inter-monsoon (SIM) and Summer monsoon (SM)) in six on–offshore stations ranging from 1 to 20 km off-shore of the Minicoy. Results indicated that the tuna larvae aggregate in the near reef waters and total tuna larvae abundance (all the species combined) shows a decreasing trend towards off-shore. Tuna larvae are found to be more abundant during SM and FIM. Comparison of the species-wise variation in tuna larvae for one season (SM) indicated that the larvae of Euthunnus affinis (32.5%) dominated among the tuna species, followed by Auxis spp. (31.6%), Thunnus spp. (3.9%) and Katsuwonus pelamis (2.7%). A pattern of highest larvae abundance in the near reef areas was observed except for Thunnus larvae. GAM indicated that mean seawater temperature and mean seawater salinity are the major environmental factors that significantly influence the larvae abundance, particularly for Thunnus followed by Katsuwonus pelamis, E. affinis and Auxis spp. The study confirms that the environmental parameters show high variation between stations and among transects as a result of the complex oceanographic characteristics around the islands. Further studies with better understanding of the larvae dynamics and their association with the environmental parameters including physical processes are essential to elucidate these relationships more clearly.